The Urgency of Islamic Education in Shaping Religious Character to Improve Students' Moral Quality - Eni Miftahul Jannah; Winna Nabillah; Nabila Syafinka Putri (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The purpose of this research is to understand the urgency of Islamic education in improving moral quality. The method used in this study is descriptive analysis. In this research, the descriptive analysis method is specifically applied, which not only describes but also provides explanations and draws conclusions from the discussed material. This research is qualitative in nature. The article discusses the important role of Islamic education in shaping religious character to enhance students' moral quality. Islamic religious education equips children with an understanding of religious values, introduces them to religious teachings, and fosters obedience to Allah SWT. Meanwhile, moral education helps children understand the difference between right and wrong, and develop good attitudes and empathy towards others and the environment. The following are the details of the urgency of Islamic education in shaping religious character to improve students' moral quality: 1) It provides physical and spiritual growth, thus forming a personality that thinks before acting; 2) It enhances the ability to manage thoughts on how to behave appropriately and correctly; 3) It fosters self-confidence and gratitude; 4) It shapes an Islamic personality and respect for others; 5) It anticipates negative influences.